Manufacturing of Human Umbilical Cord Mesenchymal Stromal Cells on Microcarriers in a Dynamic System for Clinical Use - Petry, Florian; Smith, Robert; Leber, Jasmin; Salzig, Denise; Czermak, Peter; Weiss, Mark L. (My University, 2016)
The great properties of human mesenchymal stromal cells (hMSCs) make these cells an important tool in regenerative medicine. Because of the limitations of hMSCs derived from the bone marrow during isolation and expansion, hMSCs derived from the umbilical cord stroma are a great alternative to overcome these issues. For a large expansion of these cells, we performed a process transfer from static culture to a dynamic system. For this reason, a microcarrier selection out of five microcarrier types was made to achieve a suitable growth surface for the cells. The growth characteristics and metabolite consumption and production were used to compare the cells growth in 12-well plate and spinner flask. The goal to determine relevant process parameters to transfer the expansion process into a stirred tank bioreactor was achieved.
Citation: Florian Petry, J. Robert Smith, Jasmin Leber, Denise Salzig, Peter Czermak, and Mark L. Weiss, “Manufacturing of Human Umbilical Cord Mesenchymal Stromal Cells on Microcarriers in a Dynamic System for Clinical Use,” Stem Cells International, vol. 2016, Article ID 4834616, 12 pages, 2016. doi:10.1155/2016/4834616